An Afrocentric Treatise of Psalm 105 as an Instructional Song on Historical Divine Exclusivity - Ndoga, Sampson (Journal for Semitics, 2025)
The use of songs for instructional purposes is a shared tradition in both African folk culture and the Hebrew scriptures. This article examines Psalm 105 as a song which emphasises divine exclusivity, drawing connections to African song traditions that serve to preserve essential beliefs for future generations. While all psalms were originally sung, their melodies have been lost over time, though they continue to be used in liturgical contexts. However, scholarly analysis of the psalms as songs has declined. This article begins by exploring the role of songs in African traditional cultures as tools for information retention and teaching, highlighting their parallels with the psalms. It then provides an analysis of Psalm 105 and concludes with the implications of viewing the psalms through the lens of song.
paid
Keywords: Afrocentric; Psalm 105; covenant; holistic; instructional; songs; ubuntu